2011
DOI: 10.1055/s-0031-1296504
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and Acquired Drug Resistance in Malignant Tumors

Abstract: Drug resistance is the major reason for failure in cancer chemotherapy. Resistance may be either pre-existent (intrinsic resistance), or induced by drugs (acquired resistance), So far, no strategy has been found to overcome resistance, which is based on highly complex and individually variable biological mechanisms. In present clinical practice, drug resistance can only be recognized during treatment, after long lag times. Thus diagnostic tests are re quired, indicating resistance at an earlier stage, in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
104
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(105 citation statements)
references
References 12 publications
1
104
0
Order By: Relevance
“…Treatments of cervical cancer usually consist of chemotherapy, radiotherapy and surgery, but these treatments still have the side effect to the patients. Lippert et al (2008) state most of the drugs used for anti-cancer are expensive, highly toxic and also having side effect such as resistance mechanism. Therefore, many researchers conduct the research on used medicinal plants to overcome the cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Treatments of cervical cancer usually consist of chemotherapy, radiotherapy and surgery, but these treatments still have the side effect to the patients. Lippert et al (2008) state most of the drugs used for anti-cancer are expensive, highly toxic and also having side effect such as resistance mechanism. Therefore, many researchers conduct the research on used medicinal plants to overcome the cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, at present, intrinsic or acquired multidrug resistance (MDR) represents a major obstacle for successful cancer chemotherapy (4). The mechanism underlying MDR is complex due to interactions between various factors, including drug efflux, the alteration of drug targets, DNA damage repair, cell proliferation and apoptosis, and cell cycle changes (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…By binding to the covalent complex formed by Top1 and DNA, CPTs prevent the re-ligation of DNA, which leads to persistent DNA breaks, subsequently inducing cell apoptosis [2] . Clinical data show that the efficiency of CPTs varies between patients, and the resistance mechanism remains to be determined [3] . Previous studies indicated that the resistant phenotype may be the result of inadequate drug accumulation in cancer cells, alterations in the target Top1 and alterations in cellular drug responses including DNA repair and apoptosis [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%